Portrait of John Steinbeck - McClanahan, Preston:::Creator::::::::::::; Hayman, Lee Richard:::Contributor::::::::::::
Portrait of John Steinbeck from the Writer's yearbook 1963 (34): 10. Hard copy found in the Steinbeck Center at PS 3537 .T3234 A14 1963g.